1995
DOI: 10.1074/jbc.270.15.8867
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Regulatory Domain of Gizzard Calponin

Abstract: Earlier, we proposed that the interaction of gizzard calponin with F-actin, promoting the inhibition of the actomyosin ATPase activity, involves the NH2-terminal portion of the calponin segment Ala145-Tyr182 (Mezgueldi, M., Fattoum, A., Derancourt, J., and Kassab, R. (1992) J. Biol. Chem. 267, 15943-15951). In this work, we have directly probed this region for actin binding sites using five peptide analogs covering different stretches of the sequence Thr133-Ile163. Co-sedimentation with F-actin, actomyosin ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
101
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(107 citation statements)
references
References 38 publications
6
101
0
Order By: Relevance
“…Thus, it was first demonstrated that the major calmodulin-binding sites reside in the chymotryptic fragments corresponding to the COOH-terminal region of caldesmon (Wang et al, 1991b). Synthetic peptides corresponding to residues 658-666 (Zhan et al, 1991) and 675-695 (Mezgueldi et al, 1994) in chicken gizzard h-caldesmon were later shown to bind calmodulin in a Ca 2+ -dependent manner. Using recombinant fragments, Marston et al (1994) proposed that Ca 2+ -calmodulin interacts with three distinct caldesmon sites: residues 658-666 (site A), residues 687-695 (site B), and residues 717-726 (site B′).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it was first demonstrated that the major calmodulin-binding sites reside in the chymotryptic fragments corresponding to the COOH-terminal region of caldesmon (Wang et al, 1991b). Synthetic peptides corresponding to residues 658-666 (Zhan et al, 1991) and 675-695 (Mezgueldi et al, 1994) in chicken gizzard h-caldesmon were later shown to bind calmodulin in a Ca 2+ -dependent manner. Using recombinant fragments, Marston et al (1994) proposed that Ca 2+ -calmodulin interacts with three distinct caldesmon sites: residues 658-666 (site A), residues 687-695 (site B), and residues 717-726 (site B′).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that Ca 2+ -calmodulin interacts with three sites in chicken gizzard caldesmon: (Zhan et al, 1991;Marston et al, 1994;Mezgueldi et al, 1994). Each of the three sites contains a Trp residue, which is believed to be involved in calmodulin binding as has been shown by fluorescence measurements (Shirinsky et al, 1988).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In all these cases calponin was eluted from the affinity matrix at about 70-100 mM of the salt and interaction of calponin with desmin is comparable with two other thin-filament-associated proteins. Limited chymotrypsinolysis of calponin results in production of long 22 kDa N-terminal and short 13 kDa C-terminal fragments [15] (Fig. 4).…”
Section: 4 6 8 112 14 16mentioning
confidence: 99%
“…Calponin Proteolysis-Calponin was digested with ␣-chymotrypsin (Sigma) (19) with the Staphylococcus aureus V8 protease (Roche Molecular Biochemicals). V8 fragments were purified by reverse phase HPLC using a Vydac C18 column developed with a 0 -100% water acetonitrile gradient containing 0.1% trifluoroacetic acid.…”
Section: Methodsmentioning
confidence: 99%